Synergistic effects of platelet-rich fibrin and photobiomodulation on bone regeneration in MC3T3-E1 Preosteoblasts - Ling-Hung Chou; Tzu-Sen Yang; Pei-Chun Wong; Ying-Chun Chen (Photodiagnosis and Photodynamic Therapy)
Background: Platelet-rich fibrin (PRF) and Photobiomodulation (PBM) are established methods for promoting bone healing. PRF enhances cell proliferation and migration due to its rich concentration of growth factors, while PBM stimulates tissue repair through mitochondrial activation. Despite their efficacies, no in-depth studies have explored the synergistic effects of combining PRF and PBM. Methods: PRF was prepared at 50 % and 100 % concentrations, and PBM was applied using an 830 nm near-infrared laser at a dose of 5 J/cm². Cell viability, migration, and calcium deposition were assessed over seven and fourteen days. Results: The combination of PRF and PBM significantly improved cell viability, migration, and calcium deposition, with the most notable effects observed after seven and fourteen days. However, a slight decrease in calcium deposition was noted in the 100 % PRF combined with the PBM group, suggesting a potential feedback mechanism at higher PRF concentrations. Conclusions: This study explores the synergistic effects of PRF and PBM, offering new insights into optimizing bone tissue engineering strategies. The findings highlight the potential of this combined approach in enhancing bone regeneration, although further research is needed to refine the optimal conditions for these therapies.